2006
DOI: 10.1124/mol.105.020537
|View full text |Cite
|
Sign up to set email alerts
|

Pseudolarix Acid B, a New Tubulin-Binding Agent, Inhibits Angiogenesis by Interacting with a Novel Binding Site on Tubulin

Abstract: Tubulin-binding agents have received considerable interest as potential tumor-selective angiogenesis-targeting drugs. Herein, we report that pseudolarix acid B (PAB), isolated from the traditional Chinese medicinal plant Pseudolarix kaempferi Gordon, is a tubulin-binding agent. We further demonstrate that PAB significantly and dose-dependently inhibits proliferation, migration, and tube formation by human microvessel enthothelial cells. It is noteworthy that PAB eliminated newly formed endothelial tubes and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 27 publications
(26 reference statements)
3
68
0
Order By: Relevance
“…Pseudolaric acid B inhibits angiogenesis by reducing the stability of HIF-1α and thereby downregulating the VEGF-VEGFR axis [15,16,18] . However, there has been no direct evidence indicating any association between its antiangiogenic activity and its inhibition of microtubulin [23,24] . By contrast, MFTZ-1 does not affect either the degradation of HIF-1α protein or the level of HIF-1α mRNA.…”
Section: Hif-1α-vegf Axis Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pseudolaric acid B inhibits angiogenesis by reducing the stability of HIF-1α and thereby downregulating the VEGF-VEGFR axis [15,16,18] . However, there has been no direct evidence indicating any association between its antiangiogenic activity and its inhibition of microtubulin [23,24] . By contrast, MFTZ-1 does not affect either the degradation of HIF-1α protein or the level of HIF-1α mRNA.…”
Section: Hif-1α-vegf Axis Inhibitorsmentioning
confidence: 99%
“…Pseudolaric acid B has been demonstrated to both elicit potent anticancer effects by depolymerizing microtubulin [22,23] and circumvent tumor multidrug resistance [22] . Detailed structure-activity studies have revealed that the components of pseudolaric acid B that are essential to its anticancer activity include a hydrophobic group (-CO 2 Me or -Me) at C-7, a Δ 7 double bond, an acyloxy (OAc) at C-4,3 and a side chain with a conjugated double bond and a hydrophilic terminal group [33] .…”
Section: Ecm Component Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…PAB also showed strong cytotoxic activity. In our collaboration study, this compound was found for the first time to have strong antiangiogenic activity with a unique mode of antitumor action [118][119][120] . A structural modification of PAB was thus conducted, and more than 40 derivatives were prepared in the first round.…”
Section: Miscellaneousmentioning
confidence: 99%